Catalyst for removing soot as well as preparation method and application of catalyst
By preparing metal oxide catalysts with ultra-thin nanosheet interwoven three-dimensional network structure, the problems of high catalyst cost and low activity in the prior art are solved, and efficient soot removal and CO2 selectivity are achieved.
Patent Information
- Application Number
- CN202411814223.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-10
AI Technical Summary
It is difficult to develop low-cost, high oxidation activity and excellent thermal stability catalysts in the prior art, especially in the field of soot catalytic combustion, porous nanosheet catalyst applications are relatively scarce.
By mixing and freeze-drying the carbon source, template agent and nitrogen source, a nitrogen doped carbon network material is prepared, and impregnated and calcined in a metal salt solution, a metal oxide catalyst with an ultra-thin nanosheet interwoven three-dimensional network structure is prepared.
The catalytic activity of the catalyst on soot particles and CO2 selectivity is significantly improved, and the method is simple and efficient, and it is suitable for a variety of metal oxides.
Smart Images

Figure CN119633871A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of catalytic combustion of soot, and in particular to a catalyst for removing soot, and a preparation method and application thereof. Background Art
[0002] Diesel engines are widely used due to their high efficiency, energy saving, durability and strong adaptability to harsh environments. However, the exhaust gas emitted by incomplete combustion contains particulate matter (PM), nitrogen oxides (NO x ), hydrocarbons (HC), carbon monoxide (CO) and other harmful pollutants, which seriously threaten human health and the ecological environment. In order to reduce diesel exhaust pollution, the diesel particulate filter (DPF) technology, as a direct and effective treatment method, has achieved remarkable results in the removal of soot particles. Combining DPF technology with catalytic oxidation technology can further remove soot particles efficiently. Therefore, the development of low-cost, high-oxidation-activity and excellent thermally stable catalysts has become a key demand.
[0003] Compared with precious metals, CeO2, Co3O4, MnO x Due to their high cost-effectiveness and excellent redox ability, isovalent metal oxides show broad application prospects in the field of soot catalytic combustion and have been widely used in the catalytic reactions of soot, CO and VOCs.
[0004] In addition, the catalytic combustion of soot is a gas-solid-solid multiphase reaction process, and the contact efficiency between soot particles and catalysts has an important influence on the catalytic activity. Porous nanosheet catalysts are superior to traditional mesoporous catalysts in soot oxidation catalytic activity because they can significantly improve the contact efficiency between soot and catalysts. However, the current research on metal oxide nanosheets mainly focuses on the composite growth of nanosheet arrays or other substrates, and porous nanosheet materials used for soot catalytic oxidation are relatively scarce. Therefore, it is urgent to develop a new type of porous nanosheet catalyst that can effectively increase the contact area between soot particles and catalysts, and improve the catalytic activity and selectivity for CO2 to meet the high-efficiency requirements of soot removal. Summary of the invention
[0005] The object of the present invention is to provide a catalyst for soot removal, a preparation method and an application thereof, wherein the catalyst for soot removal has high catalytic activity for soot particles and high selectivity for CO2.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a catalyst for removing soot, comprising the following steps:
[0008] mixing a carbon source, a template agent and water, and freeze-drying the resulting mixed solution to obtain a freeze-dried sample;
[0009] The freeze-dried sample is mixed with a nitrogen source and calcined to obtain a nitrogen-doped carbon network material;
[0010] The nitrogen-doped carbon network material is dispersed in a metal salt solution, impregnated with heat preservation, and then calcined to obtain a catalyst for soot removal;
[0011] The metal elements in the metal salt solution include one or more of cobalt, manganese, cerium and nickel.
[0012] Preferably, the carbon source includes glucose, fructose or starch, the template includes sodium chloride or sodium silicate, and the molar ratio of the carbon source to the template is 1:60-70; the concentration of the carbon source in the mixed solution is 0.1-0.15 mol / L, and the concentration of the template is 5-6 mol / L.
[0013] Preferably, the freeze-drying temperature is -60°C to -80°C, and the time is 24 to 48 hours.
[0014] Preferably, the nitrogen source includes urea, ammonium chloride or amino acid compounds; the mass ratio of the nitrogen source to the carbon source is 1:1 to 1.5.
[0015] Preferably, the calcination temperature is 650-700° C. and the calcination time is 120-150 min.
[0016] Preferably, the metal salt in the metal salt solution includes cobalt nitrate hexahydrate, manganese acetate tetrahydrate, cerium nitrate hexahydrate or nickel nitrate hexahydrate.
[0017] Preferably, the concentration of the metal salt solution is 0.5 to 1 mol / L; the concentration of the nitrogen-doped carbon network material in the metal salt solution is 0.06 to 0.1 g / mL.
[0018] Preferably, the temperature of the heat preservation impregnation is 35-45° C., and the time is 10-12 hours; the temperature of the roasting is 500-550° C., and the time is 120-150 minutes.
[0019] The present invention provides a catalyst for removing carbon smoke prepared by the above preparation method.
[0020] The present invention provides application of the above-mentioned catalyst for soot removal in the field of soot catalytic combustion.
[0021] Beneficial effects of the present invention:
[0022] The present invention uses green and cheap carbon sources, templates and nitrogen sources as raw materials, and prepares a nitrogen-doped carbon fiber template with an ultra-thin nanosheet interwoven three-dimensional network structure by freeze-drying, and loads a variety of variable valence metals on the template by impregnation to prepare a metal oxide catalyst. The obtained metal oxide catalyst not only has a three-dimensional network structure interwoven by ultra-thin nanosheets, but also has a rich and evenly distributed mesoporous structure; this unique morphological structure is conducive to the distribution and diffusion of soot particles, so that the soot particles can smoothly enter the interior of the catalyst and achieve full contact with the metal oxide particles. The catalyst prepared by the present invention significantly improves the catalytic activity of soot particles and the selectivity of CO2, and the method is universal, not only applicable to transition metals, but also applicable to lanthanide metals, and most metal oxides can present a three-dimensional network-like porous nanosheet morphology.
[0023] The catalyst preparation process of the present invention is simple and efficient, and uses green and cheap raw materials, which conforms to the concept of green synthesis. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the XRD diagram of the catalyst for soot removal in Example 1;
[0025] Figure 2 This is the XRD diagram of the catalyst for soot removal in Example 2;
[0026] Figure 3 This is the XRD diagram of the catalyst for soot removal in Example 3;
[0027] Figure 4 This is the XRD diagram of the catalyst for soot removal of Example 4;
[0028] Figure 5 This is a scanning electron microscope image of the nitrogen-doped carbon network material prepared in Example 1;
[0029] Figure 6 Example 1 Soot Removal Catalyst NCN-Mn x O y SEM images of
[0030] Figure 7 This is a scanning electron microscope image of the soot removal catalyst NCN-NiO of Example 2;
[0031] Figure 8 This is a scanning electron microscope image of the soot removal catalyst NCN-Co3O4 of Example 3;
[0032] Fig. 9 This is a scanning electron microscope image of the soot removal catalyst NCN-CeO2 of Example 4;
[0033] Fig.10It is a comparison chart of the soot conversion rate of the soot removal catalysts of Examples 1 to 4 and the pure soot when no catalyst is added. DETAILED DESCRIPTION
[0034] The present invention provides a method for preparing a catalyst for removing soot, comprising the following steps:
[0035] mixing a carbon source, a template agent and water, and freeze-drying the resulting mixed solution to obtain a freeze-dried sample;
[0036] The freeze-dried sample is mixed with a nitrogen source and calcined to obtain a nitrogen-doped carbon network material;
[0037] The nitrogen-doped carbon network material is dispersed in a metal salt solution, impregnated with heat preservation, and then calcined to obtain a catalyst for soot removal;
[0038] The metal elements in the metal salt solution include one or more of cobalt, manganese, cerium and nickel.
[0039] In the present invention, unless otherwise specified, the required raw materials for preparation are all commercially available products well known to those skilled in the art.
[0040] In the present invention, the carbon source and the template agent are preferably dissolved in water, stirred and mixed, and the obtained mixed solution is freeze-dried until the water is completely removed to obtain a freeze-dried sample.
[0041] In the present invention, the carbon source preferably includes glucose, fructose or starch, further preferably includes glucose or fructose, and more preferably is glucose; the template preferably includes sodium chloride or sodium silicate, and more preferably is sodium chloride; the molar ratio of the carbon source to the template is preferably 1:60-70, further preferably 1:60-65, and more preferably 1:60-62; the concentration of the carbon source in the mixed solution is preferably 0.1-0.15 mol / L, and more preferably 0.1 mol / L, and the concentration of the template is preferably 5-6 mol / L, further preferably 5.5-6 mol / L, and more preferably 5.69-6 mol / L.
[0042] In the present invention, the freeze-drying temperature is preferably -60°C to -80°C, more preferably -80°C, and the time is preferably 24 to 48 hours, more preferably 48 hours.
[0043] The present invention preferably grinds the freeze-dried sample and the nitrogen source until they are uniformly mixed, places the obtained mixture in a tubular furnace, calcines under nitrogen protection, cools to room temperature, washes the residual material with water, and obtains a nitrogen-doped carbon network material after drying, which is recorded as N-CN; the present invention mixes the carbon source and the template agent for freeze-drying and then grinds the freeze-dried sample with the nitrogen source, thereby improving the efficiency of freeze-drying.
[0044] In the present invention, the nitrogen source preferably includes urea, ammonium chloride or amino acid compounds, further preferably includes urea or ammonium chloride, and more preferably is urea; the mass ratio of the nitrogen source to the carbon source is preferably 1:1 to 1.5, and further preferably is 1:1.
[0045] In the present invention, the calcination temperature is preferably 650-700°C, more preferably 650°C, and the time is preferably 120-150 min, more preferably 120 min; the drying temperature is preferably 60-80°C, and the time is preferably 3-6 h.
[0046] The present invention preferably disperses the nitrogen-doped carbon network material in a metal salt solution, places the obtained suspension in a water bath for heat preservation and impregnation, filters after impregnation, collects the filter residue, and dries at 80°C. The dried sample is calcined in a muffle furnace to obtain a catalyst for soot removal; in the present invention, the metal salt in the metal salt solution preferably includes cobalt nitrate hexahydrate, manganese acetate tetrahydrate, cerium nitrate hexahydrate or nickel nitrate hexahydrate, further preferably includes cobalt nitrate hexahydrate, manganese acetate tetrahydrate or cerium nitrate hexahydrate, and more preferably includes cobalt nitrate hexahydrate or cerium nitrate hexahydrate; the concentration of the metal salt solution is preferably 0.5-1 mol / L, and more preferably 1 mol / L; the concentration of the nitrogen-doped carbon network material in the metal salt solution is preferably 0.06-0.1 g / mL, and more preferably 0.06 g / mL.
[0047] In the present invention, the temperature of the heat preservation impregnation is preferably 35-45°C, more preferably 35°C, and the time is preferably 10-12h, more preferably 12h; the temperature of the roasting is preferably 500-550°C, more preferably 500°C, and the time is preferably 120-150min, more preferably 120min, and the heating rate to the roasting temperature is preferably 2°C / min.
[0048] The present invention also provides a catalyst for removing carbon smoke prepared by the above preparation method.
[0049] The present invention also provides an application of the soot removal catalyst in the field of soot catalytic combustion, wherein the mass ratio of the soot removal catalyst to soot is preferably 8:1 to 10:1, the reaction temperature is preferably 650 to 700°C, and the reaction rate is preferably 2 to 5°C / min.
[0050] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0051] Example 1
[0052] 1.25 g of glucose and 25 g of NaCl were dissolved in 75 mL of water, and the resulting mixed solution was freeze-dried at -80 °C for 48 h until the water was completely removed to obtain a freeze-dried sample;
[0053] The freeze-dried sample was mixed with 1.25 g of urea and ground evenly. The resulting mixture was placed in a tubular furnace and calcined under nitrogen protection at a temperature of 650 ° C for 120 min. After calcination, the mixture was cooled to room temperature, and the residual material was washed with water and dried at 80 ° C for 6 h to obtain a nitrogen-doped carbon network material, which was recorded as N-CN.
[0054] 300 mg N-CN was dispersed in 50 mL of 1 mol / L tetrahydrate manganese acetate aqueous solution, and the obtained suspension was placed in a water bath for heat preservation and impregnation, and was kept warm in a water bath at 35°C for 12 hours. After the impregnation was completed, it was filtered, and the filter residue was collected and dried at 80°C for 5 hours. The dried sample was calcined, and the temperature was increased to 500°C at a rate of 2°C / min, and the calcination time was 120 minutes. After cooling, the catalyst for carbon soot removal of Example 1 was obtained, which was recorded as NCN-Mn x O y .
[0055] Example 2
[0056] The only difference from Example 1 is:
[0057] The metal salt solution is nickel nitrate hexahydrate aqueous solution;
[0058] The soot removal catalyst of Example 2 was obtained and was recorded as NCN-NiO.
[0059] Example 3
[0060] The only difference from Example 1 is:
[0061] The metal salt solution is a cobalt nitrate hexahydrate aqueous solution;
[0062] The soot removal catalyst of Example 3 was obtained and was recorded as NCN-Co3O4.
[0063] Example 4
[0064] The only difference from Example 1 is:
[0065] The metal salt solution is a cerium nitrate hexahydrate aqueous solution;
[0066] The soot removal catalyst of Example 4 was obtained and was recorded as NCN-CeO2.
[0067] Characterization and performance determination
[0068] 1. The soot removal catalysts obtained in Examples 1 to 4 were analyzed by X-ray diffractometer to obtain Figures 1 to 4 .
[0069] like Figure 1 As shown in the XRD diagram, the peaks of Mn2O3 and Mn3O4 appeared. Therefore, the catalyst obtained in Example 1 contains Mn2O3 / Mn3O4 mixed oxides, which are recorded as NCN-Mn x O y .
[0070] Figure 2 The peak of the sample is consistent with the standard spectrum of NiO, indicating that the material contains NiO, proving the successful synthesis of the material NCN-NiO. Figure 3 The sample peaks are consistent with the standard spectrum of Co3O4, indicating that the material contains the same spectrum, proving the successful synthesis of NCN-Co3O4. Figure 4 The sample peaks are consistent with the standard spectrum of NCN-CeO2, indicating that the material contains NCN-CeO2, proving the successful synthesis of NCN-CeO2.
[0071] 2. The morphologies of the nitrogen-doped carbon network material prepared in Example 1 and the soot removal catalysts prepared in Examples 1 to 4 were observed using a scanning electron microscope. Figures 5 to 10 :
[0072] Figure 5 This is a scanning electron microscope image of the nitrogen-doped carbon network material prepared in Example 1. Figure 1 As shown, N-CN as a template is a 3D network-like structure composed of ultrathin nanosheets;
[0073] Figure 6 Example 1 Soot Removal Catalyst NCN-Mn x O y SEM images of Figure 6 As shown in the figure, the material is a three-dimensional network structure interwoven by ultra-thin nanosheets, on which abundant mesopores and metal particles are distributed. This unique morphology can fully contact with soot particle clusters and individual soot particles.
[0074] Figure 7 This is a scanning electron microscope image of the soot removal catalyst NCN-NiO in Example 2. Figure 7 As shown, the material has a large number of obvious holes, around and inside the holes, metal particles are clustered;
[0075] Figure 8 This is a scanning electron microscope image of the soot removal catalyst NCN-Co3O4 of Example 3. Figure 8As shown, the material retains the ultrathin nanosheet structure of the template N-CN as a whole, and is distributed with a large number of mesopores and metal particles;
[0076] Fig. 9 This is a scanning electron microscope image of the soot removal catalyst NCN-CeO2 of Example 4. Fig. 9 As shown, the material is a unique three-dimensional network structure composed of porous nanosheets, which indicates the presence of a large number of voids or channels inside it.
[0077] 3. The surface area, pore size and pore volume of the soot removal catalysts prepared in Examples 1 to 4 were measured using the BET method. The results are shown in Table 1:
[0078] Table 1 Specific surface area, pore diameter and pore volume of the catalyst for soot removal of Examples 1 to 4
[0079]
[0080]
[0081] Combined with Table 1, it can be seen that the pore volume and pore diameter of the soot removal catalysts in Examples 1 to 4 are relatively large, and the specific surface area is high. Among them, the surface area of the catalyst material prepared in Example 3 is as high as 110.18 m 2 / g.
[0082] 4. A temperature programmed oxidation (TPO) reaction was carried out in a fixed bed microreactor. The fixed bed microreactor was connected with an infrared flue gas analyzer to measure the conversion rate of the soot removal catalysts of Examples 1 to 4 on the oxidation reaction of soot (model carbon black particles Printex-U) at different temperatures. The results are shown in Tables 2 and Fig.10 ;
[0083] TPO reaction:
[0084] Use a spoon to mix 50 mg of soot removal catalyst and 5 mg of soot (mass ratio 10:1) in a small beaker to achieve a loose contact mode; in a pure N2 atmosphere, the temperature was raised to 100°C at a rate of 5°C / min and kept warm for 10 minutes to pretreat the sample; in a reaction atmosphere of 10 vol% O2 / N2, the temperature was raised from 100°C to 650°C at a rate of 2°C / min to carry out TPO reaction.
[0085] Table 2 Conversion rate of the catalyst for soot removal in Examples 1 to 4 and its T 50 CO2 selectivity
[0086]
[0087] Fig.10The soot conversion rate comparison diagram of the soot removal catalysts for Examples 1 to 4 of the present invention and the pure soot when no catalyst is added is shown in Table 2 and Fig.10 It can be seen that the temperature of the catalysts obtained in Examples 1 to 4 of the present invention when the soot conversion rate is 10% is between 357 and 376°C, indicating that the catalysts of the present invention have high catalytic activity; Sample NCN-Mn x O y T 50 412℃, (T 50 The CO2 selectivity at 97.7%; the T 50 409℃, The selectivity of Example 2 to CO2 was the best when the soot conversion rate was 50%, which indicated that the porous and rough surface structure was conducive to the catalytic combustion of soot. The T 50 399℃, The T of the catalyst NCN-Co3O4 obtained in Example 3 is 98.8%. 50 (the temperature when the soot conversion rate is 50%) is the lowest, which indicates that a large specific surface area can greatly improve the catalytic activity of the catalyst for soot combustion; the T 50 432℃, The carbon soot removal performance of Example 3 is the best.
[0088] It can be seen from the above Examples 1 to 4 that the present invention provides a catalyst for soot removal, which has a three-dimensional network structure interwoven by ultrathin nanosheets, and the nanosheets are also provided with abundant mesopores and evenly distributed metal particles, which are beneficial to the catalytic combustion of soot particles. The obtained catalyst has high catalytic activity for soot combustion and high selectivity for CO2.
[0089] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a catalyst for removing soot, characterized in that: The following steps are involved: mixing a carbon source, a template agent and water, and freeze-drying the resulting mixed solution to obtain a freeze-dried sample; The freeze-dried sample is mixed with a nitrogen source and calcined to obtain a nitrogen-doped carbon network material; The nitrogen-doped carbon network material is dispersed in a metal salt solution, impregnated with heat preservation, and then calcined to obtain a catalyst for soot removal; The metal elements in the metal salt solution include one or more of cobalt, manganese, cerium and nickel.
2. The preparation method according to claim 1, characterized in that: The carbon source includes glucose, fructose or starch, the template includes sodium chloride or sodium silicate, and the molar ratio of the carbon source to the template is 1:60-70; the concentration of the carbon source in the mixed solution is 0.1-0.15 mol / L, and the concentration of the template is 5-6 mol / L.
3. The preparation method according to claim 1, characterized in that: The freeze-drying temperature is -60°C to -80°C, and the time is 24 to 48 hours.
4. The preparation method according to claim 1, characterized in that: The nitrogen source includes urea, ammonium chloride or amino acid compounds; the mass ratio of the nitrogen source to the carbon source is 1:1 to 1.
5.
5. The preparation method according to claim 1, characterized in that: The calcination temperature is 650-700° C. and the calcination time is 120-150 minutes.
6. The preparation method according to claim 1, characterized in that: The metal salt in the metal salt solution includes one or more of cobalt nitrate hexahydrate, manganese acetate tetrahydrate, cerium nitrate hexahydrate and nickel nitrate hexahydrate.
7. The preparation method according to claim 1, characterized in that: The concentration of the metal salt solution is 0.5-1 mol / L; the concentration of the nitrogen-doped carbon network material in the metal salt solution is 0.06-0.1 g / mL.
8. The preparation method according to claim 1, characterized in that: The temperature of the heat preservation immersion is 35-45° C., and the time is 10-12 hours; the temperature of the roasting is 500-550° C., and the time is 120-150 minutes.
9. The soot removal catalyst prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the soot removal catalyst according to claim 9 in the field of soot catalytic combustion.
Citation Information
Patent Citations
Nitrogen-doped carbon material with high nitrogen content as well as preparation method and application thereof
CN106892416A
Porous nitrogen-doped carbon-based transition metal monatomic catalyst as well as preparation method and application thereof
CN113351236A
Mn-doped Co-based catalyst as well as preparation method and application thereof
CN115430431A
N-doped ordered mesoporous carbon adsorption material as well as preparation and application thereof
CN115999510A
Preparation method of three-dimensional high-specific-surface-area high-entropy metal oxide oxygen evolution catalyst
CN116949487A